Distinctive features of the new consumer contract law - Whittaker, S (Sweet and Maxwell, 2017)
Discusses four aspects of consumer contract law after the enactment of the Consumer Contracts (Information, Cancellation and Additional Charges) Regulations 2013, the Consumer Protection (Amendment) Regulations 2014 and the Consumer Rights Act 2015: (1) the information duties of traders; (2) the rules on the binding force of contract; (3) consumer rights and remedies; and (4) the law's relationship with the enforcement of consumer protection.